Verokannustimet innovaatiopolitiikan välineenä - Tanja Tanayama; Pekka Ylä-Anttila (The Research Institute of the Finnish Economy (ETLA), 2009)
Subsidies to business sector R&D can be given either as R&D tax credits or direct grants. Majority of the OECD countries use both policy tools, Finland has used only grants. The Finnish support system has been functioning relatively well, but it has been argued that it does not support well enough the small and medium sized companies and startups. The paper reviews evaluation results from other small countries which show that tax credits usually have a positive impact on the amount of business R&D, especially in the group of SMEs. The report concludes that in case Finland introduces tax credits as innovation policy tool, the system should be designed transparent and straightforward. A proper evaluation and information gathering should be designed as part of the system.
Keywords: H25; O38; 330; Innovation policy; R&D subsidy; tax credit; Innovationspolitik; Forschungssubvention; Steuerbegünstigung; Finnland